Clinical Evaluation of the Failures in Fixed Partial Dentures - Magdi Mohamed Iswalhia, Amal Emhemed Benjareed, (Pakistan Journal of Medical & Health Sciences, 2023)
The researchers in this study set out to do just that by investigating what goes wrong with people's permanent dental prostheses in Libya. One hundred patients from the clinic in Gharyan, Libya, who had come in complaining of problems with their fixed dental prostheses were included in the study, and the reasons for their failure were categorized using Manappallil's system. Failures in Class 3 accounted for 30% of all failures, Class 4 for 24%, Classes, 2, and 4 for 8%, Classes 5 and 6 for 15%, and Class 6 for 11%. Class 1 for 8%, Class 2 for 12%, Class 4 for 24% Class 5 for 15 % and Class 6 for 11%. Unserviceable restorations due to poor margins were indicated as the most common cause of failure in class 3 failures in the current study. Keywords: Rehabilitation, Fixed partial dentures, Failure classification, success.